Answer:
x = 7
y = 0
Explanation:
Equation: 2x - 9y = 14
We are given that x = -6y + 7
So we substitute (-6y + 7) for "x" in the equation 2x - 9y = 14
* substitute *
2 ( -6y + 7 ) - 9y = 14
now we solve for y using basic algebra
step 1 distribute the 2
2 * -6y = -12y
2 * 7 = 14
now we have -12y + 14 - 9y = 14
step 2 combine like terms
-12y - 9y = -21y
now we have -21y + 14 = 14
step 3 subtract 14 from each side
14 - 14 cancels out
14 -14 = 0
now we have -21y = 0
step 4 divide each side by -21
-21y / -21 = y
0 / -21 = 0
we're left with y = 0
now to find x
To find x we substitute 0 for "y" in x = -6y + 7
* substitute *
x = -6 ( 0 ) + 7
-6 * 0 = 0
we're left with x = 7